The Nature of Historical Research and Scientometric Methodology - Gevorgyan, Ashot; Mosinyan, Davit (Conatus - Journal of Philosophy, 2024)
Historiography regularly encounters a crisis. This is mainly due to methodological reasons. History is not a representation of the past based on some archival materials because, firstly, the past is not available, secondly, the past, and therefore the present and the future, cannot be thought anew, and the historical research will not find new facts. New methods are needed to rethink the idea of the past. Recently, indicators of the development of science are in academic journals. Therefore, their analysis will allow through comparison to highlight the lacks of the historiography’s current state and identify the perspectives of their correction.